Um método proximal inexato com distâncias proximais para problemas de equilíbrio Quase-monótono - Mallma Ramirez, Lennin (2017)
In this work we propose an inexact proximal point method to solve quasimonotone equilibrium problems using proximal distances and the diagonal subdifferential. Under some natural assumptions on the problem and the quasimonotonicity condition on the bifunction, we prove that the sequence generated for the method converges to a solution point of the problem.